Hypercalcemia episodes caused by ectopic parathyroid adenoma and subsequent gastrointestinal stromal tumor: A case report and literature review - Lin, Yi-Ching; Lee, Jen-Chieh; Wen, Chen-Yu; Chiu, Wei-Yih (Frontiers in Oncology, 2025)
ObjectiveEctopic parathyroid gland-induced hypercalcemia is unusual, whereas hypercalcemia from a gastrointestinal stromal tumor (GIST) is extremely rare. This study aims to present a rare case of simultaneous ectopic parathyroid adenoma and GIST, associated with two episodes of hypercalcemia, and to review imaging techniques for ectopic parathyroid localization and the mechanism of hypercalcemia linked to GISTs.MethodsThe clinical manifestations, diagnostic workup, therapeutic interventions, and outcomes of the present case were analyzed. To evaluate advanced imaging modalities, particularly four-dimensional computed tomography (4D-CT) and 18F-fluorocholine (FCH) PET/CT, for ectopic parathyroid localization, a PubMed search for literature in English from inception to July 2025 was conducted using the terms (“4D-CT” AND “ectopic parathyroid”) or (“18F-fluorocholine PET/CT” AND “ectopic parathyroid”). Additional keywords related to parathyroid imaging, including “FCH-PET/CT”, “18F-fluorocholine PET/CT”, and “4D-CT”, were incorporated to broaden the search. Reports of GIST-related hypercalcemia were also identified to summarize underlying mechanisms and management approaches.ResultsAn 87-year-old man presented with progressive renal dysfunction and hypercalcemic hyperparathyroidism. 99mTc-sestamibi single photon emission computed tomography/computed tomography (SPECT/CT) identified an ectopic parathyroid lesion in the anterior mediastinum, which was successfully treated with video-assisted thoracoscopic surgery, resolving hypercalcemia. Two years later, recurrent hypercalcemia occurred with reduced parathyroid hormone levels. A CT scan and biopsy revealed a GIST in the pelvis, an extremely rare cause of hypercalcemia. Imatinib normalized calcium and parathyroid hormone levels and induced tumor regression. Nineteen reports showed that 4D-CT or FCH-PET/CT successfully localized ectopic parathyroid lesions after conventional imaging modalities were inconclusive. In 9 cases of GIST-associated hypercalcemia, pathophysiology may involve parathyroid hormone–related protein (PTHrP) or 1-alpha-hydroxylase, with glucocorticoids having a potential role in treatment.ConclusionsTo our knowledge, this case represents the first reported coexistence of an ectopic parathyroid adenoma and a GIST. 4D-CT and FCH-PET/CT can be used as alternative imaging modalities following 99mTc-sestamibi SPECT/CT to locate ectopic parathyroid lesions. The mechanism behind GIST-related hypercalcemia may involve the expression of PTHrP or 1-alpha-hydroxylase in tumor tissues.